Predictive levels of vascular endothelial growth factor (VEGF), thymidine kinase 1(TK1) with interleukin-6 (IL-6), plasma T cells, NK cells as well as B cells in treating diffuse large B-cell lymphoma receiving rituximab: Predictive levels of vascular endothelial growth factor (VEGF), thymidine kinase 1(TK1) with interleukin-6 (IL-6) - Ye, Jiagui (Journal of Medical Biochemistry, 2025)
Aim: To explore the effect of rituximab in combination with chemotherapy in treating diffuse large B-cell lymphoma,and levels of vascular endothelial growth factor (VEGF), thymidine kinase 1(TK1) with interleukin-6 (IL-6), plasma T cells, NK cells as well as B cells.  Methods: 80 patients admitted to Lujiang County People’s Hospital from January 2022 to January 2024 were included. The control group accepted cyclophosphamide, doxorubicin, vincristine, and prednisone chemotherapy regimen. On the basis of the control group, the research group was treated with rituximab. Serum related factors. 4 mL of fasting venous blood was obtained from patients. After centrifugation, the serum was separated. The levels of vascular endothelial growth factor (VEGF), thymidine kinase 1(TK1) along with interleukin-6 (IL-6) were detected by RT-96A enzyme marker (Shenzhen Mindrays Medical Electronics Co., LTD.). The ELISA kit was purchased from Shenzhen Jingmei Biotechnology Co., LTD. Lymphocyte subsets index. Blood samples of the two groups were collected, and the plasma T cells, NK cells as well as B cells of the two groups were detected by flow cytometry. Results: The total clinical effective rate of the research group was better relative to the control group (P
Keywords: diffuse large B-cell lymphoma, rituximab, chemotherapy, lymphocyte subsets index